Integration of catalytic capability and pH-responsive wettability in a VxOy-based dual-mesh system: towards solving the trade-off between the separation flow rate and degradation efficiency. Issue 9 (5th February 2021) - Liu, Ya'nan; Qu, Ruixiang; Li, Xiangyu; Zhai, Huajun; Zhao, Shuaiheng; Wei, Yen; Feng, Lin
Abstract : A catalysis mesh and pH-responsive wettability mesh composite system has been applied for fast separation of oil/water mixtures and full degradation of water-soluble pollutants in situ . Abstract : Superwetting materials that possess the property of flow-through catalysis have been applied widely for the treatment of water contamination, due to their dual functions of simultaneous separation of oil/water phases and degradation of organic pollutants. However, there is an unavoidable antinomy between the separation flow rate and degradation efficiency, which is called the dilemma of "trade-off". Concretely, a high flow rate is essential for gravity driven separation whereas thorough degradation generally demands the contact time between materials and targets to be long enough. Herein, we proposed a vanadium oxide based dual-mesh system which is composed of one catalysis mesh folding onto one switch mesh. The switch mesh is pH controllable that turns "on" in a basic environment and turns "off" under acid or neutral conditions. Initially, the switch mesh was "off" and thus polluted water could be blocked above the switch mesh and degraded by the catalysis mesh completely. Once detecting the end of degradation, the switch was turned on by pH regulation and as a result water flowed through the system with a high flow rate and simultaneously formed a barrier to the oil phase, demonstrating the superb ability of the system to solve the "trade-off". The response of the whole system is expeditious and reiterative, and meanwhile the degradation and separation capabilities are outstanding and durable. We believe that this flexible integration of catalytic capability and pH-responsive wettability can provide inspiration for extremely efficient elimination of various pollutants from water in practice.